The Role of Echocardiography in Amniotic Fluid Embolism: A Case Series and Review of the Literature. Issue 3 (24th September 2022) - Simard, C.; Yang, S.; Koolian, M.; Shear, R.; Rudski, L.; Lipes, J.
Abstract : ( Can J Anesth / J Can Anesth . 2021;68:1541–1548) Amniotic fluid embolism (AFE) is not completely understood and can be difficult to diagnose, as it shares characteristics with other obstetric complications. AFE occurs during labor or soon after delivery and is characterized by acute hypotension, hypoxia, and coagulopathy. The Clark diagnostic criteria for diagnosis of AFE is as follows: sudden cardiorespiratory arrest or both hypotension and respiratory compromise; disseminated intravascular coagulation; clinical onset during labor or within 30 minutes of delivery of the placenta; and absence of fever. Situations that may lead to the exchange of maternal and fetal fluid, such as cesarean delivery or cervical trauma, have been reported as risk factors. Point-of-care echocardiography has recently been used to diagnose and manage maternal shock. This report details three cases of AFE that utilized point-of-care echocardiography.